Improving Student Outcomes Through Universal Design for Learning: A Case Study of Color Vision Deficiency in Learning Visual Design (S/O: 14513) - Sarif, Siti Mahfuzah; Muda, Suhaini; Mohamed, Nur Fadziana Faisal (UUM, 2022)
Colour Vision Deficiency (CVD) or colour-blindness could be a disadvantage for learners in the Visual Design course, as colour is one of the essential components in Visual Design. Students with CVD could be at risk of underperforming with their choice of a restricted colour palette. Meanwhile, Universal Design for Learning (UDL) provides the framework that meets the needs of every student in a classroom through its three main principles: Engagement, Representation, and Action and Expression. Hence, this study aimed to address the questions: 1) how the student with CVD perceives their learning in a visual design course and 2) how UDL can improve the outcome of the student with CVD in a visual design course. The study is conducted in one of the undergraduate courses in Universiti Utara Malaysia. Four students with CVD were identified after the screening processes. This study adopts the qualitative case study methodology and the deductive approach in analysing the qualitative data. Theory-driven codes were created to assist in the coding of the interview data and students' reflective journals. The findings show that students with CVD did appreciate the presence of assistive tools to help with colour selection (i.e., Representation), have a high interest in doing visual design tasks (i.e., Engagement), and affirmative towards the challenges they faced (i.e., Action and Expression) in Visual Design course due to the deficiency